Presenting gender research to a scientific audience - Castellanos, Paige; Sachs, Carolyn; Tickamyer, Ann R. (Pennsylvania State University, 2017)
Presented by Paige Castellanos, Carolyn Sachs and Ann Tickamyer (PSU), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017